2011
DOI: 10.4194/1303-2712-v11_3_09
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Twenty new records for freshwater algal flora of Turkey were determined in a study conducted from February 2007 to January 2009 in Ikizcetepeler and Çaygören Reservoirs, Balıkesir, Turkey. Among these new records, 4 were Bacillariophyta, 7 were Chlorophyta, 3 were Streptophyta, 1 was Cryptophyta, 3 were Dinophyta, 1 was Euglenophyta and 1 was Heterokontophyta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Glenodinium sp. has been previously reported by Sevindik et al (2011) in Çaygören Reservoir which is close to Çamköy Reservoir.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Glenodinium sp. has been previously reported by Sevindik et al (2011) in Çaygören Reservoir which is close to Çamköy Reservoir.…”
Section: Discussionsupporting
confidence: 69%
“…The total number of phytoplankton taxa (39) was lower in Çamköy Reservoir compared with the other reservoirs in the same vicinity. Sevindik et al (2011) reported 192 phytoplankton taxa from Çaygören Reservoir and 174 taxa from Ikizcetepler Reservoir. The reason for this was probably the excessive B levels in Çamköy Reservoir (Davis et al 2002;Gunes et al 2006;Marín and Oron 2007;Şaşmaz and Öbek 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Morover, many of these diatoms frequently reported from water bodies in Turkey are taxa well known in European and Asiatic areas because of seeing commonly there, too . To date, the taxa listed in the results of Ladik and Hazar sediment cores have not been recorded in Turkey (Gönülol et al, 1996;Aysel, 2005;Solak, Ector, Wojtal, Ács, & Morales, 2012;Solak et al, 2016;Ongun-Sevindik et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…According to Aysel (2005), 2030 taxa of freshwater algae had been recorded in Turkey. Since that year, new records of freshwater algae have been continuously added (Şahin 2007Baykal et al 2009;Sevindik et al 2010Sevindik et al , 2011Özer et al 2012;Akar and Şahin 2014;Yüce and Ertan 2014). The Tigris is one of Turkey's most important rivers but its algal flora is still poorly known.…”
Section: Introductionmentioning
confidence: 99%